2015
DOI: 10.1016/j.apradiso.2015.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Fully-automated synthesis of 16β- 18 F-fluoro-5α-dihydrotestosterone (FDHT) on the ELIXYS radiosynthesizer

Abstract: Noninvasive in vivo imaging of androgen receptor (AR) levels with positron emission tomography (PET) is becoming the primary tool in prostate cancer detection and staging. Of the potential 18F-labeled PET tracers, 18F-FDHT has clinically shown to be of highest diagnostic value. We demonstrate the first automated synthesis of 18F-FDHT by adapting the conventional manual synthesis onto the fully-automated ELIXYS radiosynthesizer. Clinically-relevant amounts of 18F-FDHT were synthesized on ELIXYS in 90 min with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…Total synthesis time including radiotracer reformulation was 90 min. Although synthesis time and yields are very similar to the results reported by others, it is important to note that these results were achieved using only 4 mg of [ 18 F]FDHT precursor …”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Total synthesis time including radiotracer reformulation was 90 min. Although synthesis time and yields are very similar to the results reported by others, it is important to note that these results were achieved using only 4 mg of [ 18 F]FDHT precursor …”
Section: Resultssupporting
confidence: 86%
“…It also uses 50% less [ 18 F]FDHT precursor than other methods. Decay corrected radiochemical yields, specific activity and overall synthesis time are comparable to the method published by Lazari et al . We believe that these modifications can easily be adapted to suit other automated synthesis modules.…”
Section: Quality Controlsupporting
confidence: 60%
See 1 more Smart Citation
“…Serial imaging using [ 18 F]FDG PET/CT followed the next day by [ 18 F]FB-GAcDb immunoPET/CT was conducted on mice with limited or extensive disease and on mice injected with antigen negative A20 cells as control. [25] were generated using the ELIXYS automated radiosynthesizer (Sofie Biosciences) [33]. Radiochemical purity was confirmed to be >95% by radio-HPLC, and radiochemical identity was confirmed in analytical HPLC by comparison with co-injected standard.…”
mentioning
confidence: 99%
“…About 8 y later, the first in-human PET imaging studies in castrate patients were reported by Memorial Sloan Kettering Cancer Center and Washington University (5-7). The production methodology developed by Washington University continues to be used to this day, though recent improvements have been made in the radiosynthetic chemistry (8) and to the production process by automation (9,10).…”
mentioning
confidence: 99%